Parallel Private Health Insurance in Australia: A Cautionary Tale and Lessons for Canada - Jeremiah Hurley; Rhema Vaithianathan; Thomas F. Crossley; Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2002)
Canada?s restrictions on the role of private health insurance for publicly insured physician and hospital services are unique among countries with universal, publicly funded health care systems. Pressure is mounting in Canada, however, to loosen these restrictions and create a parallel system of private finance. Advocates argue that creation of a parallel system of private finance will ensure the sustainability of the public system (by reducing public cost pressures), improve access to the public system (e.g., by reducing wait times), and improve quality in the public system (through competition). Opponents of parallel private finance argue that it will create ?two-tiered? medicine, increase costs, compromise equity and reduce quality and access to publicly financed health care as those with the financial means (and often the strongest voice) exit to private insurance. Australia provides a particularly promising case study for Canada regarding the dynamics of parallel systems of public and private finance. This paper examines Australia's experience with parallel finance for inpatient hospital services to provide insight regarding: (a) the effectiveness of a parallel system of private finance in reducing costs and wait times in the public system; (b) risk selection between the parallel public and private insurance sectors; (c) the financial redistribution associated with the introduction and maintenance of a parallel system of finance; and (d) the dynamics of the broader political economy associated with parallel systems of finance. Australia's experience provides a number of lessons for Canada, including: (1) the potential for cost savings through introduction or expansion of a parallel private sector is very limited; (2) the introduction or expansion of a parallel private finance is unlikely to reduce wait times in the publicly financed system; (3) there is no simple way to regulate private insurers to pursue public objectives; (4) it is impossible to create an independent, isolated parallel system of private finance – interactions between the public and private insurance sectors are complex and unavoidable; (5) quality plays a key role in driving the dynamics between the public and privately financed sectors; and (6) it is essential to articulate clear policy objectives for health care financing and to design public and private roles consistent with these objectives. Our overall conclusion is that the Australian experience provides a cautionary tale regarding the risks, costs and benefits of a parallel private system of health care finance.
Keywords: I18; I11; 330; health care financing; Australian health policy; Private Krankenversicherung; Gesundheitsfinanzierung; Vergleich; Australien; Kanada